The Role of Information and Communication Technology in Teaching and Learning Islamic Religious Education at SMAN 1 Galis Pamekasan - Irawati Irawati; Nisa’ul Karimah; Fitriyatul Kiptiyah; Abdul Halim; Abd. Mukhid (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The purpose of this study was to determine how information and communication technology (ICT) is used in Islamic Religious Education (PAI) classes at SMAN 1 Galis Pamekasan. This study employed descriptive qualitative techniques, using PAI teachers and students as data sources. After collecting information through observation, interviews, and documentation, the data were reduced, presented, and conclusions drawn. The research findings indicate that teachers can deliver learning materials in a more engaging and understandable manner by utilizing ICT. Students become more engaged and interested in learning PAI as a result of the use of digital media. However, the implementation of ICT-based learning still faced several obstacles, such as unstable internet connections, limited facilities, and the use of digital devices that could distract students’ concentration during learning activities. To overcome these problems, Teachers take a variety of steps to address this, including developing learning media, participating in technology training, integrating Islamic values into digital learning, and supervising the use of technology so that the learning process could remain effective and relevant to current educational needs.